Strategi Pemasaran Melalui Flywheel Marketing Formula Pada Cv Tiga Rasa Gemilang (Cireng Cipok) - Agustin, Melinda Yuni; Rita Komaladewi (Program Studi Ilmu Administrasi Bisnis FISIP UNPAS, 2024)
With the rapid development of time, business phenomena, especially in the food industry, have been evolving rapidly. So far, the marketing of CV Tiga Rasa Gemilang has been using a funnel marketing approach, which is deemed to have not produced optimal results. With the observation conducted, the author expands the marketing of Cireng Cipok using the flywheel marketing approach. The identified problems, design of the marketing plan, and analysis of the TOWS matrix are conducted. The research results project that the implementation of a flywheel marketing strategy focused on customer satisfaction can increase sales and achieve a 10% increase in revenue in the short term, with growth reaching 2.5 times in the medium term and 5 times in the long term. The development focus in the first month is on sales and online promotion. The growth of sales volume in the medium and long term develops exponentially by maintaining and expanding price variations, as well as expanding stores and implementing customer retention programs such as seasonal products, discounts, and membership.